2022
DOI: 10.1021/acscatal.2c03909
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoroisopropanol for the Selective Deactivation of Poisonous Nucleophiles Enabling Catalytic Asymmetric Cyclopropanation of Complex Molecules

Abstract: In the presence of 1,1,1,3,3,3-hexafluoroisopropanol (HFIP), nucleophilic and reactive reagents are prevented from interacting with a rhodium carbene, allowing asymmetric cyclopropanation to occur with high yield and stereoselectivity on a variety of compounds. A high-throughput screen was conducted on cyclopropanation with a complementary catalytic system in the presence of 90 different poisonous nucleophiles and varying amounts of HFIP (10 equiv, used as reaction solvent). The scope of both the aryl/heteroar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…A feature of our ligand design is the ability to monitor the coordination of a variety of species at one Rh site, and allows the evaluation of effect of the tethered, axial coordinating group at the other Rh site. This could have implications where initial coordination is important, such as competition between carbene precursors and catalyst poisons in carbene transfer reactions, [14] or off‐targeted binding of proteins in a biological context [8a,10b] . Our recent work has shown that incorporating tethered, axially coordinated thioether ligands can improve yields in cyclopropanation reactions [15] and Si−H insertion reactions [16] .…”
Section: Introductionmentioning
confidence: 99%
“…A feature of our ligand design is the ability to monitor the coordination of a variety of species at one Rh site, and allows the evaluation of effect of the tethered, axial coordinating group at the other Rh site. This could have implications where initial coordination is important, such as competition between carbene precursors and catalyst poisons in carbene transfer reactions, [14] or off‐targeted binding of proteins in a biological context [8a,10b] . Our recent work has shown that incorporating tethered, axially coordinated thioether ligands can improve yields in cyclopropanation reactions [15] and Si−H insertion reactions [16] .…”
Section: Introductionmentioning
confidence: 99%
“…In developing this method, we also tested the sensitivity of the reaction to additional changes of conditions (sensitivity screen; Scheme b). Employing a radar plot, we evaluated the reaction performance with the introduction of air and water, and variable temperature and current were assessed (Scheme b). Yield of product 2 was compared to the optimized reaction conditions (Table , entry 9) .…”
mentioning
confidence: 99%
“…The positive influence of HFIP is consistent with recent studies, demonstrating that in the reactions of donor/acceptor carbenes HFIP blocks interference by water 30 and a range of other nucleophilic poisons. 31 Having demonstrated that the C−H functionalization of benzylic sites with the diazophosphonate 4 is a viable process, an optimization study with a series of the most established chiral catalysts was conducted (Table 1 and Figure 1). The bulky triarylcyclopropanecarboxylate catalyst, Rh 2 (S-p-Br-TPCP) 4 , 32 gave only a trace of the desired product 6 (entry 2) even though it is an exceptional catalyst for C−H functionalization reactions with aryldiazoacetates.…”
mentioning
confidence: 99%
“…The positive influence of HFIP is consistent with recent studies, demonstrating that in the reactions of donor/acceptor carbenes HFIP blocks interference by water 30 and a range of other nucleophilic poisons. 31 …”
mentioning
confidence: 99%